Moderating Effect of Religiosity on the Relationship between Fraud Diamond and Accounting Fraud: Study on the Banking Sector of Indonesia - Safitri, Nurul Emil; Nurkholis, Nurkholis; Baridwan, Zaki (Journal of Accounting Research, Organization and Economics, 2023)
Objective This study examines and analyzes the effect of fraud diamond on accounting fraud, with religiosity as the moderator, among management staff in the banking sector of Indonesia.Design/methodology This study uses the primary data taken from a survey conducted on the employees and officials of 82 Regional Development Bank offices in Southeast Sulawesi, Indonesia. This study uses purposive sampling technique and 279 people were selected as respondents. This study applies quantitative method and uses 2 analysis techniques, multiple regression analysis and moderated regression analysis.Results This study finds that the higher the pressure, opportunity, rationalization, and the capability at the workplace are, the higher the likelihood of accounting fraud to occur. Further, the result of moderation regression analysis indicates that religiosity weakens the effects of pressure and rationalization on accounting fraud, but it does not moderate the influence of opportunity and capability on accounting fraud.Research limitations/implications Company leaders and staff to better understand personal and situational (organizational) factorssuch as pressure, opportunity, rationalization, and capabilitiesthat can affect individuals to avoid accounting fraud behavior.Novelty/Originality This paper presents the cases of accounting fraud caused by internal company parties and accounting fraud problems involving directors, managers, and employees. In this case, the aspects of pressure, opportunity, rationalization, and capability can be considered predictors of what affect individuals to commit accounting fraud. This is to reduce accounting fraudulence in the company. This claim is supported by those who are highly religious and are able to suppress fraudulent behaviors.